The Influence of Women on Boards on Companies’ ESG and Financial Performance in Canada - Khalili, Mazdisna (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The contemporary world requires active economic engagement of all members ofthe society so the participation of women, as half of society, seems necessary. In recent decades, the rate of gender differences in labor participation have been narrowing substantially and in developed countries especially, we observe on increasing numbers of women reaching top positions in different fields of work. In this study, we analyze whether female on boards in public Canadian companies have any significant effect on ESG and financial performance in different businesses. Thus, the aim of the research is to examine the relationship between gender management diversity, ESG score, and firm financial performance in public Canadian companies. For collecting the data, we considered the list of companies from Canadian public companies. We selected our companies based on their gender diversity which have both genders in the top managers. The total panel data is composed of 398 Canadian public companies in 2019. The result of our study indicates there is a positive significant correlation between ESG score and Female on Boards. The financial part also illustrates a statistically significant relationship between women on boards and firm financial performance. Thus, we accept H1 which women on boards in publicly listed firms in Canada are associated positively with firm financial performance and ESG score. Keywords: ESG, ROA, women on boards, financial performance

ÖZ: Çağdaş dünya, toplumun tüm üyelerinin aktif ekonomik katılımını gerektirmektedir, bu nedenle kadınların, toplumun yarısı olarak katılımı gerekli görünmektedir. Son yıllarda, işgücüne katılımdaki cinsiyet farklılıklarının oranı önemli ölçüde daralmaktadır ve özellikle gelişmiş ülkelerde, farklı çalışma alanlarında üst sıralara ulaşan kadınların sayısının arttığını gözlemliyoruz. Bu çalışmada, Kanadalı kamu şirketlerindeki kurullarda çalışan kadınların ESG ve farklı işletmelerdeki finansal performans üzerinde önemli bir etkisi olup olmadığını analiz ediyoruz. Bu nedenle, araştırmanın amacı Kanadalı kamu şirketlerinde cinsiyet yönetimi çeşitliliği, ESG puanı ve firma finansal performansı arasındaki ilişkiyi incelemektir. Veri toplamak için Kanada kamu şirketlerinden şirketlerin listesini inceledik. Şirketlerimizi, her iki cinsiyeti de üst yöneticilerde olan cinsiyet çeşitliliğine göre seçtik. Toplam panel verileri 2019 yılında 298 Kanadalı kamu şirketinden oluşuyor. Çalışmamızın sonuçları ESG skoru ile Kuruldaki Kadın arasında pozitif anlamlı bir korelasyon olduğunu göstermektedir. Mali kısım aynı zamanda kurullardaki kadınlar ile firma finansal performansı arasında istatistiksel olarak anlamlı bir ilişkiyi göstermektedir. Bu nedenle, H1, Kanada'da halka açık şirketlerdeki kurullarda bulunan kadınları firma finansal performansı ve ESG puanı ile olumlu bir şekilde ilişkilendirdiklerini kabul ediyoruz. Anahtar Kelimeler: ESG, ROA, kadın kurullarında, finansal performans
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2020. Supervisor: Prof. Dr. Turhan Çetin Kaymak.
Keywords: Business Administration; Economic development--Financial Performance--Canada; ESG; ROA; women on boards; financial performance